Enhancing Optical and Thermal Stability of Blue-Emitting Perovskite Nanocrystals through Surface Passivation with Sulfonate or Sulfonic Acid Ligands - Shu-Han Huang; Sheng-Hsiung Yang; Wen-Cheng Tsai; Hsu-Cheng Hsu (Nanomaterials, 2024)
This study aims to enhance the optical and thermal properties of cesium-based perovskite nanocrystals (NCs) through surface passivation with organic sulfonate (or sulfonic acid) ligands. Four different phenylated ligands, including sodium β-styrenesulfonate (SbSS), sodium benzenesulfonate (SBS), sodium p-toluenesulfonate (SPTS), and 4-dodecylbenzenesulfonic acid (DBSA), were employed to modify blue-emitting CsPbBr1.5Cl1.5 perovskite NCs, resulting in improved size uniformity and surface functionalization. Transmission electron microscopy and X-ray photoelectron spectroscopy confirmed the successful anchoring of sulfonate or sulfonic acid ligands on the surface of perovskite NCs. Moreover, the photoluminescence quantum yield increased from 32% of the original perovskite NCs to 63% of the SPTS-modified ones due to effective surface passivation. Time-resolved photoluminescence decay measurements revealed extended PL lifetimes for ligand-modified NCs, indicative of reduced nonradiative recombination. Thermal stability studies demonstrated that the SPTS-modified NCs retained nearly 80% of the initial PL intensity when heated at 60 °C for 10 min, surpassing the performance of the original NCs. These findings emphasize the optical and thermal stability enhancement of cesium-based perovskite NCs through surface passivation with suitable sulfonate ligands.